Gender Inequality in Jack Thorne’s Movie Enola Holmes 2 - Rindu, Septiane; Podungge, Rusni; Usu, Novi Rusnarty (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
Enola Holmes 2, a film set in the Victorian era, portrays these inequalities through its female characters who face an environment full of gender-based restrictions. This article focuses on three main characters—Enola Holmes, Sarah Chapman, and Mira Troy—analyzing how their experiences reflect various aspects of gender inequality that have persisted over time. This study analyzes gender inequality in Jack Thorne’s Enola Holmes 2 through the lens of Fakih’s theory, which identifies five manifestations of gender inequality: stereotypes, subordination, marginalization, violence, and double workload. The research applies feminist literary criticism, focusing on the socio-economic conditions and experiences of women, while also linking the findings to the reality of women in the Victorian era. Using a qualitative method, the study examines the dialogues and interactions of the three female characters in the film—Enola Holmes, Sarah Chapman, and Mira Troy—as representations of women who experience gender inequality. From the analysis, 16 instances of gender inequality were identified, illustrating the challenges faced by women during both the Victorian era and in the context of the film’s narrative. These findings reveal how gender inequality persists and is reflected in the experiences of the female characters, highlighting its continued relevance in both historical and modern contexts.